Chococrispy.SH / Muhammad Haziq Shamsul Akmal and Nur Shafiqa Athirah Abdullah - Shamsul Akmal, Muhammad Haziq; Abdullah, Nur Shafiqa Athirah (2023)
This social media portfolio report is all about the use of social media platform (Facebook) for online marketing done by Chococrispy.SH. Chococrispy.SH is dropship business located in Saujana Utama with the headquarters based in Perak and currently manage by Muhammad Haziq bin Shamsul Akmal and Nur Shafiqa Athirah binti Abdullah The business use a Facebook page to promote and market the product to the public in the form of teaser and copywriting which include the hard sell and soft sell.